Dual resonance element for broadband reflectarray antenna - M. Hashim Dahri; M.R. Kamaruddin; M.H. Jamaluddin; M. Inam; S. Z. N. Zool Ambia; N. Shafie (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
A dual resonance reflectarray unit cell element has been proposed which evolved from a square patch element to enhance its bandwidth performance. A bend in the width of the element is used to modify its dimensions and surface currents for broadband operation. The results have been analyzed in the frequency band of 24 GHz to 28 GHz. Two different combinations of its dimensions are selected for the investigating of its various performance parameters. A maximum static phase range of 432° and 255° have been obtained with selected dimensions. The wide-band features of proposed unit cell element can be used particularly to design a broadband reflectarray antenna for future fast communication systems.